A double life - Berry, Flynn, 1986- (Viking, 2018)
"A gripping, intense, stunningly written novel of psychological suspense from the award-winning author of Under the Harrow. Claire is a hardworking doctor living a simple, quiet life in London. She is also the daughter of the most notorious murder suspect in the country, though no one knows it. Nearly thirty years ago, while Claire and her infant brother slept upstairs, a brutal crime was committed in her family's townhouse. Her father's car was found abandoned near the English Channel the next morning, with bloodstains on the front seat. Her mother insisted she'd seen him in the house that night, but his powerful, privileged friends maintained his innocence. The first lord accused of murder in more than a century, he has been missing ever since"--